Rozpisać :

1.Wykonaj mnożenie i zredukuj wyrazy podobne.
a)(x+ 2)(x +4)
b) (-3x - 4)(5 - 2x)
c) (√3 +2)(2 √3 -3)
d) (2 √a - √b)(-√b + 2√a)

2.Zapisz w postaci sumy.
a)(½ + x)²
b) (2 - 5x)²
c) (a - 3b)(3b + a)
d) (-2a + 2b)²
e)(-2a -1)²
f)(⅔x - ¾y)(⅔x + ¾y)

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-07T21:20:33+01:00
1.
a)(x+ 2)(x +4)= x²+4x+2x+8= x²+6x+8
b) (-3x - 4)(5 - 2x)= - 15+6x²-20-8x=6x²-8x-35
c) (√3 +2)(2 √3 -3)= 6-3√3+4√3-6=√3
d) (2 √a - √b)(-√b + 2√a)= 2√ab+4a-b-2√ab=4a-b


2.
a)(½ + x)²= 1/4+x+x²=x²+x+1/4
b) (2 - 5x)²= 4 - 50x+ 25x²= 25x²-50x+4
c) (a - 3b)(3b + a)= 3ab+a²-9b²-3ab=a²-9b²
d) (-2a + 2b)²=4a²-8ab+4b²
e)(-2a -1)²= 4a²-4a+1
f)(⅔x - ¾y)(⅔x + ¾y)= 1 ⅓ + ½ - ½ - 9/16= 1⅓ -9/16